1999
DOI: 10.1515/hf.1999.100
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Analysis by Permanganate Oxidation. II. Lignins in Acidic Organosolv Pulps

Abstract: The permanganate oxidation method was used to analyze residual lignins in Norway spruce (Picea abies) organosolv pulps. The pulps were produced by ethanol water solvolysis catalyzed by 0.005M or 0.01M H 2 SO 4 at 175°C. Condensation reactions of residual lignin occurred at a significant rate when the ethanol volume fraction was 0 % but not when it was ≥ 51 %. There was selective removal of uncondensed guaiacyl units when mixtures of 51 %, 76%, and 91% ethanol were used. The condensed units in the native lignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…If the benzyl cation intermediate II is formed from acidic cleavage of a methoxyl group, the coupling with methanol corresponds to the reverse reaction. The possible prevention of condensation with alcohols has been discussed in a number of publications (Bose et al 1999;Evtuguin et al 2000;Oliet et al 2001), whereas no direct experimental proof has been reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…If the benzyl cation intermediate II is formed from acidic cleavage of a methoxyl group, the coupling with methanol corresponds to the reverse reaction. The possible prevention of condensation with alcohols has been discussed in a number of publications (Bose et al 1999;Evtuguin et al 2000;Oliet et al 2001), whereas no direct experimental proof has been reported so far.…”
Section: Resultsmentioning
confidence: 99%
“…MnO 2 oxidation of lignin has been examined in only a few studies, at least from a pure chemistry viewpoint, , although nonrecyclable permanganate (MnO 4 ¯) oxidation of lignin has been reported fairly widely. It is generally known that MnO 2 oxidizes allyl and benzyl alcohols selectively among various types of alcohols to afford the corresponding conjugate and aromatic carbonyls, respectively, with the oxidation rates being higher in nonpolar organic solvents than in polar solvents. MnO 2 oxidation of other alcohols progresses only under severe conditions. , However, if MnO 2 had oxidized only benzyl alcohols in the residual lignin, and consequently the corresponding α-carbonyl groups had just formed in our previous study, in accordance with this general knowledge, sufficient delignification must not have been attained. Just introducing α-carbonyl groups does not contribute to delignification at the employed pH and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…A second alkaline selfcondensation of AP was performed, and on this occasion the residual AP after alkaline treatment was 15.5%, and that value decreased to 7.7% after acidolysis (Table 7). The likely cause of AP disappearance during acidolysis is acid-catalyzed condensation of the AP to the C-6 position of other aromatic rings, which occurs at a higher rate in water alone as compared to water/solvent mixtures (Bose et al 1999). Two 8 mL aliquots of the acidified reaction products were then supplemented with 2 mL of n-propanol before being acidolyzed.…”
Section: Alkaline Lmc-xylan Reaction and Subsequent Hydrolysis Of Lccmentioning
confidence: 99%